2006
DOI: 10.1007/s10668-006-9069-9
|View full text |Cite
|
Sign up to set email alerts
|

Linking perceived land and water resources degradation, scarcity and livelihood conflicts in southwestern Tanzania: implications for sustainable rural livelihood

Abstract: In Africa, the land and water resources quality are key factors for sustainable development. The degradation of the quality of these resources leads to scarcities and conflicts, which together threaten the sustainability of rural livelihoods. This work investigated and analysed the livelihoods conflicts over the land and water resources and their scarcities, policies that contributed to the land and water scarcities and the livelihood conflicts and linkage of the conflicts to the resources scarcities and degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…In previous survey, 83% of interviewees reported that, frequencies of drought occurrence have increased and that has been due to the decline in the amount of rainfall and change in its timing. This argument was verified through analyses of data on the quantity and timing of precipitation (Malley et al 2007a). …”
Section: Increased Frequency Of Droughtmentioning
confidence: 86%
See 2 more Smart Citations
“…In previous survey, 83% of interviewees reported that, frequencies of drought occurrence have increased and that has been due to the decline in the amount of rainfall and change in its timing. This argument was verified through analyses of data on the quantity and timing of precipitation (Malley et al 2007a). …”
Section: Increased Frequency Of Droughtmentioning
confidence: 86%
“…A total of 266 households were interviewed in the six villages, the households were selected, from the three common dominant agricultural production systems in the area in a ratio of 134:67:65 of crop farmers, pastoralists, and agro-pastoralists, respectively. Households' production system identification, classification, sample size decision, sampling procedures, questionnaire development and interview procedures were detailed in Malley et al (2007a). However, for the present study, the predominantly agropastoral households (mixed farmers) responded to both the crop and the livestock productivity interviews.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without necessarily directly engaging with the way in which the notion of community has been conceptualised, a number of researchers have provided case studies that problematise the dominant assumptions seeking to explain how communities are constituted and how they co-operate (Johnson, 2001;McDaniel, 2003;Roth, 2006;Galvan, 2007;Malley et al, 2008). Within mainstream approaches it has been acknowledged in some quarters that one of the major liabilities of ideas such as community-based conservation is its titular reference to 'community', as this term is 'one of the most vague and elusive concepts in social science and [one] which continues to defy precise definition' (Murphree, 2000, p. 4).…”
Section: Critique I: the 'Homogenous Community'mentioning
confidence: 99%
“…In Tanzania, linkages of the impacts of climate change caused by environmental changes on rural livelihoods are increasingly evident (Madulu 2003;Malley et al 2007aMalley et al , 2007bMalley et al , 2008aMalley et al , 2008b. Madulu (2003) observed a strong link of poverty to change in climate.…”
Section: Introductionmentioning
confidence: 99%